2022
DOI: 10.1039/d2na00169a
|View full text |Cite
|
Sign up to set email alerts
|

Tunable physical properties in Bi-based layered supercell multiferroics embedded with Au nanoparticles

Abstract: Multiferroic materials present as an interesting functional material family combining two ferroic orderings, e.g., ferroelectric and ferromagnetic orderings, or ferroelectric and antiferromagnetic orderings, and find various device applications, such as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The BFMO SC has not been used in device fabrication in previous work. This demonstration of FeFET devices using the BFMO SC on Si opens potential for other layered multiferroic oxides, e.g., BiAlMnO and BiMoMnO, in practical device applications. Future work on integrating these new layered oxides and other multiferroic oxides on Si will be necessary for such device demonstrations.…”
Section: Resultsmentioning
confidence: 88%
“…The BFMO SC has not been used in device fabrication in previous work. This demonstration of FeFET devices using the BFMO SC on Si opens potential for other layered multiferroic oxides, e.g., BiAlMnO and BiMoMnO, in practical device applications. Future work on integrating these new layered oxides and other multiferroic oxides on Si will be necessary for such device demonstrations.…”
Section: Resultsmentioning
confidence: 88%
“…This CeO 2 re-seeding approach can also be used in other SC systems, such as the BAMO and BNMO Aurivillius phases, which have similar structures to the BFMO system. 21,23 Another potential application for this technique is the combination of multiple Aurivillius phases using CeO 2 interlayers. A preliminary demonstration is shown in the XRD data in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Despite their potential uses in memories 5,6 and spintronic devices, 7 single phase multiferroic materials are scarce due to conicting requirements of ferromagnetism (partially lled d-orbitals) and ferroelectricity (empty d-orbitals). 8 Beside the well-studied single phase multiferroic materials, such as BiFeO 3 (BFO) 9 and BiMnO 3 (BMO), 10 a new group of Bismuth-based complex oxides, including Bi 3 Fe 2 Mn 2 O x (BFMO), [11][12][13][14][15][16][17][18] Bi 2 AlMnO 6 (BAMO), [19][20][21] Bi 2 MoO 6 , 22 and Bi 2 NiMnO 6 (BNMO), 23 have shown interesting multifunctionalities, attracting attention and becoming the topic of many recent studies. Making this group of materials interesting is the growth of a unique anisotropic layered Aurivillius supercell (SC) phase and the resulting highly anisotropic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembled metal-oxide nanocomposites have generated tremendous research interest due to their fascinating functionalities and potential applications in the fields of energy harvesting devices, catalysis, magnetic data storage, and optical metamaterials. Among them, vertically aligned nanocomposites (VAN) with metal nanopillars embedded in an oxide matrix have attracted much attention because of their vertical strain coupling, strong structural and property anisotropy, enabling the epitaxial growth of large mismatched systems, and versatile material combinations coupling spin, charge, lattice, and orbital degrees of freedom. , However, due to the limited understanding of the growth kinetics in the self-assembly VAN growth process, controlling the morphology of the formed nanopillars by simply tuning the deposition parameters is usually difficult. Very uniform pillar distribution and density tuning have been demonstrated in multiple VAN systems, but with limited success in achieving ordering and morphology control of nanopillars. Lu et al demonstrated initial success in in-plane long-range ordering in the La 0.7 Sr 0.3 MnO 3 -Au system on annealed SrTiO 3 (STO) substrates with well-controlled terraces for nucleation .…”
Section: Introductionmentioning
confidence: 99%